2010
DOI: 10.1149/1.3383041
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Relaxation Effects of Ni Patterned Anodes in H[sub 2]–H[sub 2]O Atmosphere

Abstract: Patterned Ni anodes on normalY2normalO3 -stabilized ZrO2 (YSZ) represent a promising approach to determine the kinetics of electrochemical reactions in solid oxide fuel cells. Contrary to technical Ni/YSZ cermet anodes, the reaction zone for the hydrogen oxidation has the potential to be well defined. This study is focused on the reproducibility of electrochemical characterization results of patterned Ni anodes, with a parameter variation of the partial pressures of normalH2 and normalH2O , temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(130 citation statements)
references
References 27 publications
(88 reference statements)
10
119
1
Order By: Relevance
“…Patterned Ni anodes with an area of 10.25 mm × 10.25 mm were fabricated on 8.5 mol% polycrystalline Y 2 O 3 -stabilized ZrO 2 (YSZ) substrates (Itochu Ceratec Corp., Japan) using a standard photolithography process [22], the procedure is described in our previous study [8]. The design of the pattern is composed of an area of 9.25 mm × 9.25 mm with parallel Ni stripes; in this study stripes with 25 m width, a spacing of 160 m and a thickness of 800 nm are chosen.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Patterned Ni anodes with an area of 10.25 mm × 10.25 mm were fabricated on 8.5 mol% polycrystalline Y 2 O 3 -stabilized ZrO 2 (YSZ) substrates (Itochu Ceratec Corp., Japan) using a standard photolithography process [22], the procedure is described in our previous study [8]. The design of the pattern is composed of an area of 9.25 mm × 9.25 mm with parallel Ni stripes; in this study stripes with 25 m width, a spacing of 160 m and a thickness of 800 nm are chosen.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Several studies on electrooxidation, which are based on patterned Ni anodes, have been performed so far for the H 2 -H 2 O atmosphere [4][5][6][7][8]. In the most recent study, our group could attribute the observed discrepancies considering absolute values of the line specific resistance (LSR) and controversial parameter dependencies to different degradation and relaxation processes occurring during characterization of nominally stable patterned Ni anodes [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPB lines in Figure 3a appear to have an irregular shape, compared to the shape of patterned Ni electrodes on YSZ obtained elsewhere (10)(11)(12)(13). Therefore it is difficult to make a direct comparison between the performance of patterned electrodes obtained in this work and in the literature.…”
Section: Electrochemical Performance Of Laser Sintered Patterned Elecmentioning
confidence: 69%
“…The parameterization of this model was supported by combining (i) microstructural parameters evaluated by means of FIB/SEM-tomography, 61) (ii) the line specific resistance of the triple phase boundary (TPB) determined by electrochemical impedance spectroscopy (EIS) on patterned model anodes, 62) (iii) the conductivity of the YSZ-matrix including the impact of NiO interdiffusion 63), 64) and (iv) the DRT as an additional quality criterion in the fitting procedure. 48) Please note, without considering the above mentioned parameters, a fitting of the spectra with even lower error levels would be possible.…”
Section: )mentioning
confidence: 99%